La catastrofe come occasione: Etnografie dal sisma emiliano tra engagement e possibile consulenza - Pitzalis, Silvia; Ciccaglione, Rita (Antropologia Pubblica, 2024)
This essay is the result of two studies conducted in the Bassa Emiliana, where an earthquake occurred in May 2012. Specific interlocutors are the members of the committee Sisma.12 and the storekeepers of Mirandola’s old town. Considering the bottom-up practices observed and the international disaster management as complementary and interacting frames, these two ethnographies show the dual rhetoric of “opportunity” and the ways in which local people interact with it. If in the former case the notion of opportunity is declined into practices of “critical” resilience that aim to increase political participation, in the latter the meaning assumed reveals the incorporation of the “capitalism of disasters”. These two cases disclose the interactive dynamics generated by local reactions to public intervention, considering the position of social actors towards management apparatus. Thus, the political commitment and the public role that the anthropologist assumes in the environment of disaster has to clarify the politicization processes visible during these situations, emphasizing choices and decisions that derive from and determine the contextual practices. Over the course of the first ethnography, a militant praxis is assumed as a prevalent methodology; in the latter case, ethnography is viewed as a form of counseling for lay actors. Finally, both the studies wish for the ethnographic encounter to involve the subjects in a game of mutual reflexivity as it can constitute the key of an intrinsically political engagement in the practice of this branch of knowledge.